2019
DOI: 10.1080/16000889.2019.1601987
|View full text |Cite
|
Sign up to set email alerts
|

Assessing moisture sources of precipitation in the Western Pamir Mountains (Tajikistan, Central Asia) using deuterium excess

Abstract: Air moisture of oceanic origin can be subject to long-range transport and could contribute to precipitation at distant places. With ongoing climate change the relationship between water vapour sources and sinks is under constant evolution and plays an important role for water budget assessments. This study analysed monthly integrated and event-based precipitation samples from two field sites in the Western Pamir Mountains (Tajikistan) for stable isotope compositions of oxygen (d 18 O) and hydrogen (d 2 H) of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 60 publications
3
22
0
Order By: Relevance
“…The source of the moisture is the most important predictor of the isotope content of precipitation [1,8]. There are numerous numerical models to study moisture sources, but a Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) [9] model has been used in numerous stable isotope studies for tracking moisture sources of precipitation [5,10,11]. Some of these studies, such as [11], consider d-excess as reliable fingerprints to study moisture sources responsible for precipitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The source of the moisture is the most important predictor of the isotope content of precipitation [1,8]. There are numerous numerical models to study moisture sources, but a Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) [9] model has been used in numerous stable isotope studies for tracking moisture sources of precipitation [5,10,11]. Some of these studies, such as [11], consider d-excess as reliable fingerprints to study moisture sources responsible for precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous numerical models to study moisture sources, but a Hybrid Single-Particle Lagrangian Integrated Trajectory (HYSPLIT) [9] model has been used in numerous stable isotope studies for tracking moisture sources of precipitation [5,10,11]. Some of these studies, such as [11], consider d-excess as reliable fingerprints to study moisture sources responsible for precipitation. Moisture released from water bodies with a high sea surface temperature (SST) and a low relative humidity normally show a high d-excess (d-excess = δ 2 H − 8 × δ 18 O [12]), whereas precipitation originating from water bodies with a low SST and a high relative humidity will normally have a moderate to low d-excess [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Data availability. Sample data can be accessed on the PANGAEA online data repository (https://doi.org/10.1594/PANGAEA.911474; Juhlke et al, 2020). Third party data used in this study include data from the IAEA/WMO GNIP program and the Copernicus Climate Change Service (C3S).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have found that evaporation and water rock interaction can increase the δ 18 O in the water, then leading to the decrease of d-excess [33,34]. In this study, the d-excess of RW samples ranges from −4.5 to 5.7‰ (mean = −0.2‰), which is lower than the d-excess value of atmospheric precipitation ( Table 1 and Figure 5), and therefore, the river water might have been affected by evaporation.…”
Section: The Evolution Of Hydrogen and Oxygen Isotopesmentioning
confidence: 99%